ENERGY- AND ENVIRONMENTALLY EFFICIENT BUILDING MIXTURES FOR 3D PRINTING - Dvorkin, Leonid; Marchuk, Vitalii; Zhitkovsky, Vadym (European Science, 2025)
The work shows the possibility of obtaining fine-grained concrete mixtures and concretes using mechanochemical activated cement-ash binders, which can be used as working mixtures for a 3D printer. The choice of raw materials solve the problem of resource